PEMBUATAN METIL ESTER SULFONAT DARI METIL ESTER BERBASIS CRUDE PALM OIL DENGAN VARIASI WAKTU DAN AGENT SULFONASI: MANUFACTURING METHYL ESTER SULFONATE FROM CRUDE PALM OIL-BASED METHYL ESTER WITH VARIATION OF TIME AND SULFONATION AGENT - Dian Anisa Destryanti; Jaksen; Selastia Yuliati (Politeknik Negeri Sriwijaya, 2022)
Surfactants are chemical compounds that are surface active that can reduce surface tension. Methyl Ester Sulfonate (MES) is an anionic surfactant that can be produced from the reaction of methyl esters made from vegetable oils with sulfonating agents. Palm oil is vegetable oils that can be produced as MES surfactants. This study aims to make MES from methyl esters based on Crude Palm Oil (CPO) with various sulfonating agents (NaHSO3; Na2S2O5; H2SO4 ) and time variations (120; 150; 180; 210; 240 minutes). To speed up the reaction in the sulfonation process, the addition of a 2% Al2O3 catalyst was used. The process of making MES is through the sulfonation process, the next process is the process of purification, neutralization, and drying. The results obtained the best sulfonating agent, namely Na2S2O5 at 240 minutes with a surface tension value of 26.2421 dyne/cm, an acid number of 1.6830 mg KOH/g MES and emulsion stability up to 10 minutes.